Membangun Keuangan Berkelanjutan Dengan Inklusi Finansial Dan Akuntansi Hijau: Mediasi Kinerja Sosial Dan Investa si Berisiko - ADANAN SILABAN; SUNDAY ADE SITORUS; Raya Panjaitan; Palti Agustinus Silaban (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study examines the influence of sustainable finance on financial inclusion and green accounting, with the mediating roles of social performance and investment risk in renewable energy companies in Indonesia. A quantitative approach was employed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with data collected from 30 renewable energy firms. The results reveal that sustainable finance significantly enhances the adoption of green accounting practices and broadens financial inclusion. Furthermore, social performance and investment risk serve as strong mediating variables in these relationships. The findings highlight the importance of integrating sustainable financial strategies to build transparent environmental reporting systems and strengthen access to formal financial services. This research proposes an integrative model linking five key variables in support of Indonesia’s green economic transition and provides both theoretical and practical contributions to the development of corporate sustainability frameworks in the renewable energy sector.